Mortalidade juvenil em São Carlos, SP, de 2000 a 2010: uma década de mudança? - Medeiros, Thaís Juliana (Universidade Federal de São Carlos, 2012)
Preoccupation about youth mortality by external causes has been a constant theme for the last decades in Brazil, because, according to Violence Map 2010, youthful homicide rate changed from 30 in 100.000 youths in 1980 to 50,1 in 2007. A better understanding of this scenario is necessary, in special in São Carlos (SP), city known to have the lower index of vulnerability against youths in 2010 (IBGE). So the research s aim was to analyze youth mortality data by external causes (traffic accidents, suicide, homicide and police shock) in São Carlos between the years 2000 and 2010 and municipal public policies which could contribute with IBGE s award. It was used the following methodological procedures: bibliographic research; data collection related to youths died by external causes at Health Information Center (CIS) in São Carlos; quantitative analysis of collected data; and interviews with municipal secretaries from 2001 to 2010. From epidemiological informations obtained and interviews with municipal managers it was verified that is not possible to set a corrrelation from public policies and youth mortality reduction in São Carlos in the last eleven years.
Keywords: Saúde pública; Mortalidade; Violência urbana; Violência - aspectos sociais; Juventude; Políticas públicas; Adolescência; Mortality; Public Policies; Youth; Adolescence, Violence; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL